2022
DOI: 10.3390/genes13010119
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Simian Endogenous Retrovirus (SERV) Full-Length Proviruses in Old World Monkey Genomes

Abstract: Simian endogenous retrovirus, SERV, is a successful germ line invader restricted to Old World monkey (OWM) species. (1) Background: The availability of high-quality primate genomes warrants a study of the characteristics, evolution, and distribution of SERV proviruses. (2) Methods: Cercopithecinae OWM genomes from public databases were queried for the presence of full-length SERV proviruses. A dataset of 81 Cer-SERV genomes was generated and analyzed. (3) Results: Full-length Cer-SERV proviruses were mainly fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that many Old World Monkey species have either full length or near full-length simian endogenous retroviral sequences (SERSs) as a result of heterozygous integrations. As described by van der Kuyl and colleagues, most SERSs are of < 0.3 and 10 million years old 16 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies have shown that many Old World Monkey species have either full length or near full-length simian endogenous retroviral sequences (SERSs) as a result of heterozygous integrations. As described by van der Kuyl and colleagues, most SERSs are of < 0.3 and 10 million years old 16 .…”
Section: Introductionmentioning
confidence: 89%
“…Most of the observed EVEs from simian virus (SIV), a retrovirus which relies on genomic insertion for replication, have undergone mutations for a long period of time. Thus, EVEs of SIV in macaques provide additional information for the study of primate evolution and medical application 16 . Previous studies have shown that many Old World Monkey species have either full length or near full-length simian endogenous retroviral sequences (SERSs) as a result of heterozygous integrations.…”
Section: Introductionmentioning
confidence: 99%
“…SERVs exist as two types: Cer-SERV-1 and Cer-SERV-2 [ 235 ]. The sequences within the LTR of Cer-SERV-1 are approximately 484 nt in length and encode five to eight TF-binding motifs (CREB, CDP, E2F, AREB6, FoxD3, FoxJ2, and Brn-2), shown in Table 2 [ 235 ].…”
Section: Tfs Associated With Erv Ltr Activation In Other Speciesmentioning
confidence: 99%
“…SERVs exist as two types: Cer-SERV-1 and Cer-SERV-2 [ 235 ]. The sequences within the LTR of Cer-SERV-1 are approximately 484 nt in length and encode five to eight TF-binding motifs (CREB, CDP, E2F, AREB6, FoxD3, FoxJ2, and Brn-2), shown in Table 2 [ 235 ]. As FoxD3 and FoxJ2 are expressed in embryonic stem cells and during early embryonic development, respectively [ 234 , 257 ], Cer-SERV-1 may also be expressed in embryonic stem cell and during early embryonic development.…”
Section: Tfs Associated With Erv Ltr Activation In Other Speciesmentioning
confidence: 99%
See 1 more Smart Citation